STRESS LEVEL OF MEDICAL STUDENTS IN ONLINE LEARNING DURING COVID-19 PANDEMIC AND ITS IMPACT ON ACADEMIC ACHIEVEMENT - Tjang, Yanto Sandy; Prihatiningsih, Titi Savitri; Prabandari, Yayi Suryo (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2023)
research on its prevalence is still very few and inconclusive. The relationship between stress and academic achievement in medical students remains a matter of debate. This study aims to determine the stress level of medical students in online learning during the COVID-19 pandemic and its impact on academic achievement.Method: This descriptive-analytical study used a cross-sectional design on undergraduate medical students from the 2019-2021 class. The questionnaire distributed online contained questions related to characteristics of respondents, 14 questions from DASS-42 questionnaire to measure stress, and questions related to respondents' perceptions of online learning and semester achievement index (IPS). Data were analysed descriptively and analytically using logistic regression method with the help of SPSS Statistics 26 software. Results: Of 431 students, 411 (95%) students participated in this study. The prevalence of stress in respondents was 41.8%, majority was mild (13.4%) and moderate (13.9%). Lack of interaction between lecturers and students increased 1,691 times the risk of stress. A total of 403 (98.1%) respondents had IPS ≥ 3. Stress on respondents did not have negative impact on academic achievement, although statistically not significant (OR = 0.831; 95% CI = 0.196-3.524; p-value 0.801).Conclusion: The prevalence of stress for medical students in online learning during COVID-19 is quite high, majority was mild and moderate. Lack of interaction between lecturers and students increased risk of stress. Majority of respondents have good IPS. Stress on respondents apparently did not have negative impact on academic achievement.